Abortion Access in the United States: A View on the Ground - Michael Stambolis-Ruhstorfer (IdeAs)
An interview with Amber Eisenmann, trainer of Clinical Staff with Essential Access Health, Los Angeles, and formerly with Planned Parenthood of Maryland. This interview was conducted on September 8th 2023.